Effect of Oxygen-Dependent Antimicrobial Systems on Legionella pneumophila - Lochner, Janis E. (1983)
Legionella pneumophila was susceptible to the antimicrobial action of oxygen metabolites generated by both the myeloperoxidase-H(2)O(2)-halide and the xanthine oxidase systems.